John Banks: an independent and itinerant lecturer of natural and experimental philosophy at the threshold of the English industrial revolution - Soares, Luiz Carlos (Circumscribere International Journal for the History of Science, 2017)
In eighteenth-century England, courses of natural and experimental philosophy delivered by independent and/or itinerant lecturers, whose textbooks and syllabi were based on Newtonian physics, became the main instruments for spreading and popularizing the idea of applied science. This effectively represented the application of the results of scientific knowledge to the population’s needs and to the production of the material components of life. Thus, the activities of independent and/or itinerant lecturers, with their courses and publications, helped to spread knowledge on the principles of mechanical and experimental science among the men who became protagonists of their country’s transformation into the first industrial power in the world. One among those lecturers was John Banks (1740–1805), who offered courses and specialized knowledge on mechanical physics and machinery to many manufacturers, engineers and mechanics, who stood at the forefront of England’s industrial transformation and was himself one of the main intellectual exponents of this process.